Slow manifesto : Lebbeus Woods blog - Woods, Lebbeus; Jacobson, Clare, 1965- (2015)
"In the fall of 2007, architect and educator Lebbeus Woods (1940-2012), long-admired for his visionary architecture and mastery of drawing, began a blog. This blog consists of articles, drawings, anecdotes, poetry, interviews, and photographic essays, and eventually grew to amass more than three hundred entries by its end in the summer of 2012. It became a repository that explores topics ranging from architectural theory and criticism to education and politics, and is regarded by many as the most comprehensive and accessible archive of Woods's creativity: it not only contains his own intricate and fascinating work, but it also stands as a fragmentary essay of the nature of architecture, asking questions at once socially urgent and provocative of the imagination. This part-forum, part-public journal engaged an immediate audience in its intimacy and personality, while impressing upon the general community an intellectual rigor on par with any academic treatise. Lebbeus Woods Blog: Outsider Architecture and Other Postings is an edited volume of the blog's centerpiece entries, together forming a collection inspirational and dear to architects, students, and thinkers"--
Keywords: Woods, Lebbeus -- Blogs; ARCHITECTURE / General